klamytewoc

## Answered question

2022-03-01

Prove that $x-\frac{{x}^{3}}{3!}<\mathrm{sin}\left(x\right) for all x>0

### Answer & Explanation

OxicegeWheegeb0k

Beginner2022-03-02Added 3 answers

Recursive integration We know that
$0\le \mathrm{cos}a\le 1⇒\mathrm{sin}t={\int }_{0}^{t}\mathrm{cos}sds
for $0. Integrating over $\left(0,z\right)$ we get
$1-\mathrm{cos}z={\int }_{0}^{z}\mathrm{sin}tdt<{\int }_{0}^{z}tdt=\frac{{z}^{2}}{2}$
that is for all $0 we have,
$1-\frac{{z}^{2}}{2}<\mathrm{cos}z\le 1$
integrating again over $\left(0,x\right)$ we get
$x-\frac{{x}^{3}}{6}={\int }_{0}^{x}1-\frac{{z}^{2}}{2}dz<{\int }_{0}^{x}\mathrm{cos}zdz=\mathrm{sin}x$
that is
$x-\frac{{x}^{3}}{6}<\mathrm{sin}x
continuing with this process you get,
$1-\frac{{x}^{2}}{2}<\mathrm{cos}x<1-\frac{{x}^{2}}{2}+\frac{{x}^{4}}{24}$
$x-\frac{{x}^{3}}{6}<\mathrm{sin}x
More generally for $n\ge 1$, by induction we get
$\sum _{k=0}^{2n-1}{\left(-1\right)}^{k}\frac{{x}^{2k}}{\left(2k\right)!}<\mathrm{cos}x<\sum _{k=0}^{2n-1}{\left(-1\right)}^{k}\frac{{x}^{2k}}{\left(2k\right)!}+\frac{{x}^{4n}}{\left(4n\right)!}$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?